INNOVATIVE TEACHING METHODS AS A COMPONENT OF THE EDUCATIONAL ENVIRONMENT OF A MODERN INSTITUTION OF HIGHER MILITARY EDUCATION - Pampukha, Ihor; Vovkotecha, Oleksandr; Kubiavka, Mykola; Pyrogov, Kyrylo (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . In the higher military educational institutions of the leading countries of the world, training methods today are mainly aimed at the development of individual qualities of cadets, in particular, critical thinking and a sense of responsibility for one's actions. During training, in most institutions, active methods are used to encourage cadets to think creatively and implement their abilities in practice. For greater efficiency in the mastering of the educational material, it is also worth using methods aimed at memorization, in particular the mind maps, reference notes, zettelkasten. The purpose of the article: to determine effective methods for learning the educational material during the training of cadets in institutions of higher military education.M e t h o d s . The content analysis of the scientific literature was used, which describes the methods of improving the mastering of educational material; quantitative and qualitative methods of scientific literature research; systematic analysis of the practical problems of using methods to improve the mastering of the material; a systematic approach to the study of methods for improving the mastering of the material; the method of analogies and comparisons to determine the most effective methods for improving the mastering of the material and the method of expert evaluations.R e s u l t s . Practical observation of cadets during testing showed that the choice of answer is often not based on knowledge of the material of the discipline, but on some other considerations. Moreover, the widespread introduction of testing formed in a significant part of cadets a persistent motivation to simply "pass" the discipline, which affects the level of their intellectual development and, ultimately, the level of their professional training This feature can be eliminated thanks to the use of innovative approaches to increase the level of the mastering of the educational material, namely the methods like mind maps, zettelkasten, reference notes, an example of the use of which is given in the work.C o n c l u s i o n s . At present, approaches to increasing the level of the mastering of educational material remain unpopular, i.e., such teaching methods that are aimed not only at the simplification and accessibility of teaching disciplines, but also at full feedback from students. It is the approaches to increase the level of the mastering of educational material, which are based on the so-called intellectual cards, mind maps, reference signals, etc., that should also have a place among the generally accepted methods of conducting classes.
Keywords: educational environment; mind maps, zettelkasten, reference notes, teaching methods